Pathophysiological Significance of Neutrophilic Transfer RNA-Derived Small RNAs in Asymptomatic Moyamoya Disease - Li, Lingzhi (Cells, 2021)
Understanding asymptomatic moyamoya disease (aMMD), for which treatment options are currently limited, is key to the development of therapeutic strategies that will slow down the progression of this disease, as well as facilitate the discovery of therapeutic targets for symptomatic MMD. Newly found transfer RNA-derived small RNAs (tsRNAs) perform potential regulatory functions in neovascularization, which is a well-known pathological manifestation of MMD. In this study, the neutrophilic tsRNA transcriptome in aMMD was profiled using next-generation RNA sequencing in five patients and five matched healthy subjects. A negative binominal generalized log-linear regression was used to identify differentially expressed (DE)-tsRNAs in aMMD. Gene Ontology and functional pathway analyses were used to identify biological pathways involved with the targeted genes of the DE-tsRNAs. Four tsRNAs were selected and validated using quantitative reverse transcription polymerase chain reaction. In total, 186 tsRNAs were DE between the two groups. Pathophysiological events, including immune response, angiogenesis, axon guidance, and metabolism adjustment, were enriched for the DE-tsRNAs. The expression levels of the four DE-tsRNAs were consistent with those in the neutrophilic transcriptome. These aberrantly expressed tsRNAs and their targeted pathophysiological processes provide a basis for potential future interventions for aMMD.